Diagnosis of hypertension in patients at the dental reception (Эндодонтия Today)
A review of a literature of the dental care to patients who have arterial hypertension was submitted. The prevalence of this pathology among the population and the role of primary diagnostic by dentists of this disease were identified. The importance of measuring blood pressure in each patient by dentist for the purpose of prevention of emergency condition was also identified.